Inference of gene regulatory metwork (GRN) rrom gene expression data using k-means clustering and entropy based selection of interactions - Galib, Asadullah Al; Rahman, Mohammad Mohaimanur (2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.